Pengaruh Metode Perkawinan Terhadap Keberhasilan Kebuntingan Sapi Donggala Di Kabupaten Sigi - Sudirman Sudirman (Mitra Sains, 2016)
This studywas conducted Januari to Mei 2015 to evaluate effect of mating method on the pregnancy success oflocal cows in Sigi Regency. The study involved 50 local cows as acceptors. The data were analyzed byusing chi-square method. The observed variables werenon-returnrate (NRR), the conception rate (CR) on thefirst mating, and that average of mating rate requiredto getpregnant.The research result showed that mating method did not influence(P>0.05) on both NRR and NR. The NRR rate were 68% and 64% for artificial insemination and natural mating, respectively. The CR were 64% and 52% for artificial insemination and natural mating, respectively. While service per conception (S/C) for artificial insemination was 1.6 and natural mating was 1.9. It is concluded that the mating method did not have asignificant effect (P>0.5)on the pregnancy success oflocal cows in Sigi Regency